A coccolithophore concept for constraining the Cenozoic carbon cycle - Henderiks, J; Rickaby, R (Copernicus Publications, 2007)
An urgent question for future climate, in light of increased burning of fossil fuels, is the temperature sensitivity of the climate system to atmospheric carbon dioxide (pCO2). To date, no direct proxy for past levels of pCO2 exists beyond the reach of the polar ice core records. We propose a new methodology for placing a constraint on pCO2 over the Cenozoic based on the physiological plasticity of extant coccolithophores. Specifically, our premise is that the contrasting calcification tolerance of various extant species of coccolithophore to raised pCO2 reflects an "evolutionary memory" of past atmospheric composition. The different times of evolution of certain morphospecies allows an upper constraint of past pCO2 to be placed on Cenozoic timeslices. Further, our hypothesis has implications for the response of marine calcifers to ocean acidification. Geologically "ancient" species, which have survived large changes in ocean chemistry, are likely more resilient to predicted acidification.